PENINGKATAN EKONOMI MASYARAKAT MELALUI HOMESTAY SYARI’AH DI KECAMATAN AMPEK ANGKEK NAGARI LAMBAH - Afri Yongki; Khadijah Nurani (Adisam Publisher, 2025)
This research is motivated by the fact that sharia homestays are a form of halal tourism development in Indonesia. Sharia homestay is a business in the field of providing accommodation that operates and is guided by sharia principles. The public still lacks knowledge regarding indicators and classification of sharia homestays. Sharia homestays are sometimes considered a business that is only intended for Muslim communities, even though basically sharia homestays are open to all groups, both Muslim and non-Muslim communities. The aim of this research is to find out how much influence and improvement the community's economy has had through sharia homestays run in Nagari Lambah, Ampek Angkek District. This research uses a descriptive qualitative research method. Data collected using interview techniques. Researchers use this type of field research, namely research that is directly carried out in the field. The people of Nagari Lambah take advantage of the tourism opportunities that exist in Nagari Lambah to improve their economy. Situations like this make Homestays empowered, because the more visitors who come to travel, the more income the community gets. There is a transformation of increasing welfare from the main livelihood to additional livelihoods and then there is a shift in the main income of the people of Nagari Lambah, where previously homestays were used as additional income, now homestays have become core income without abandoning the previous livelihood.